PERAN BUDAYA ORGANISASI SEKOLAH MEMODERASI PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KOMPETENSI TERHADAP KINERJA GURU SMP SE-KECAMATAN KESESI KABUPATEN PEKALONGAN - 11.52.02.0046, Yusuf (Jurnal Mahasiswa Pasca Sarjana, 2013)
This research aim to analyze the role of school organization culture moderate the influence of school principalâs leaderships and competence to teacher performance in SMP at Kesesi district of Pekalongan residenceThe population in this research is all SMP teachers at Kesesi district of Pekalongan residance there were 134 people. Data colleting methode is use quesionery. The measurement use likert scale on 7 alternative answers. Instrument measurement with validaty and realibity test. The classic assumption test using normality test, heterokedastisty test, and mulicoloneriety test. While testing model using coeficient determination test and F test (goodnes of fit). Hiphotesys test by using regresion analyze.The result of research is showing that (i) teacher competances is positif and significant influence to teacher performance (ii) school principalâs leadership is positif and significant influence to teacher performance, (iii) school organization culture is positif and significant influence to teacher performance, (iv) school organization culture not moderate the influence of teacher competence to teacher performance (v) school organization culture not moderate the influence of school principalâs leadership to teacher performance. Key words:Â Â Â Â Â Â teacher competence, the school principalâs leadership, school organization culture, teacher performance Â